PENGARUH ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI UD. CENTRAL MART SAMADAYA HILISIMAETANO - Novitasari Laowo (Jurnal Ilmiah Mahasiswa Nias Selatan, 2023)
The purpose of this study is to determine the influence of product attributes on consumers' purchasing decisions at UD. Central Mart Samadaya Hilisimaetano. The type of research used is a quantitative type of causal nature. The source of the data was from consumers, with the population and sample in this study being 36 respondents. Data collection techniques are research instruments or questionnaires. The data analysis method used is a simple regression analysis Y=2.093+0,867X. The results of this study showed that the counting value was 6,659>table of 1,691. This research can be concluded that there is an influence of product attributes on consumer purchasing decisions in UD. Central Mart Samadaya Hilisimaetano. The suggestions of this study are (1) To improve purchasing decisions, consumers must pay attention to the level of consumer needs, the condition of similar competitors in providing services, the presence of attractive discounts or discounts, the existence of a comfortable waiting room so that it is able to provide comfort more optimally and so on. (2) UD. Central Mart Samadaya needs to maintain or enlarge the market share if the set is enough to attract consumers, then it is likely that consumers will not move to other products.